Data leakage prevention system based on transparent encryption for mobile terminal equipment - Zhen-tao HUANG; Nuan HE; An-min FU; Bo-yu KUANG; Guang-hua ZHANG (Tongxin xuebao)
With the trend that enterprise key data moves to mobile terminal,data leakage prevention has become an im-portant issue on mobile terminal.To solve the problem,a pre-decryption transparent encryption technology was set up which solved the problem that traditional transparent encryption technology only can ensure application layer security,in addition,performance on mobile was improved.At the same time,taking advantage of the idea of combining thin client and mobile terminal to prevent leakage of data,a virtual remote desktop technology on mobile was proposed,which completely shield the shortcomings of data transmission and ensure the safe transmission of mobile terminal data.Finally,a data leakage pre-vention system for mobile terminal was set up,which makes the mobile terminal fully and effectively protected.